2022
DOI: 10.1155/2022/4376968
|View full text |Cite|
|
Sign up to set email alerts
|

Thoracoscopic Lobectomy versus Segmentectomy in the Treatment of Patients with Early-Stage Lung Cancer

Abstract: Objective. To assess the clinical efficacy of thoracoscopic lobectomy and segmentectomy in the treatment of patients with early-stage lung cancer. Methods. A total of 70 patients with early-stage non-small cell lung cancer who were treated in our hospital from April 2018 to May 2020 were recruited and assigned at a ratio of 1 : 1 to receive either segmentectomy (observation group) or lobectomy (control group). Outcome measures included clinical efficacy, surgery-related indicators, pulmonary function indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Relevant studies have pointed out that the higher the level of self-efficacy of patients, the more positive of the patients to cope with the disease, resulting in better prognosis and quality of life [24]. The results of this study showed that the total self-efficacy score of patients in the observation group was significantly higher than that of the control group, indicating that TIR nursing can enhance the sense of self-efficacy of patients after radical surgery.…”
Section: Discussionmentioning
confidence: 57%
“…Relevant studies have pointed out that the higher the level of self-efficacy of patients, the more positive of the patients to cope with the disease, resulting in better prognosis and quality of life [24]. The results of this study showed that the total self-efficacy score of patients in the observation group was significantly higher than that of the control group, indicating that TIR nursing can enhance the sense of self-efficacy of patients after radical surgery.…”
Section: Discussionmentioning
confidence: 57%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%